Effect of Cassava (Manihot esculenta Crantz: Euphorbiaceae) Starch on the Stabilization of Malagasy Lateritic Soil - Harinivo Olsynthique Razanajatovo; Serge Ravelomanantsoa; Elise Octavie Rasoazanany; Aristote Matondo; Colette Masengo Ashande; Muhammad Ridwan; Koto-te-Nyiwa Ngbolua; Robijaona Rahelivololoniaina Baholy (Budapest International Research and Critics University, 2020)
Laterite is one of the most widespread raw materials, especially in Madagascar. Its valorization as a building material would help to solve many socio-economic problems in Madagascar as well as in Africa. The use of this type of material fits well within the framework of high environmental quality, since the process uses an abundant material that does not require too much energy for its manufacture because it is dried in the open air. The aim of this work was to stabilize the laterite with cassava starch. The valorization of the latter would contribute to the development of new building materials. The study focuses on the mechanical characterization of specimens made with Vontovorona laterite in different proportions, which goes hand in hand with the determination of the physico-chemical parameters of the starch. To make specimens, we used techniques such as extraction, sieving, heating, laterite-stabilizing dosage, mixing, rotting, moulding, clamping, demoulding, drying. The results obtained show that the best stabilizing material is obtained if 15% of starch is mix to lateritic soil. The compressive strength in the dry state of the test specimens (samples) gave a significantly interesting result with a value of 54.8 bars (85% laterite with 15% starch). Thus the use of starch as a stabilizer in construction gave satisfactory results. This eco-friendly process, simple in its steps and practice, should be popularized among artisanal brick makers. Thus, replacing proportions of the Portland cement in soil stabilization with Cassava starch will reduce the overall environmental impact of the stabilization process.